An exploration of the role of visuals and users’ imagery and verbal preferences on goal attainment and coaching chatbot adoption - Nicky Terblanche; Yaron Prywes (International Journal of Evidence Based Coaching and Mentoring)
Artificial intelligence chatbots could scale coaching, however user adoption is a challenge. We investigate the effect of images on chatbot adoption and coaching efficacy by comparing a text-only coachbot (TextBot, n=126) with a text+images bot (ImageBot, n=116). We measure goal attainment and technology adoption one week apart, as well as users’ preferences for imagery and verbal modes of communication. Perceived goal attainment increased at T2 for both bots. If “Correct word usage” was important, users found the TextBot to be less “fun”. Users with lower “Imagination” also found the TextBot easier to use, and were more likely to use it. We introduce the concept of “AI coach customization”.